FTY720 (Fingolimod) sensitizes hepatocellular carcinoma cells to sorafenib‐mediated cytotoxicity. Issue 5 (19th August 2015) - Ahmed, Dilruba; de Verdier, Petra J.; Ryk, Charlotta; Lunqe, Oscar; Stål, Per; Flygare, Jenny
Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer‐related death worldwide. The multityrosine kinase inhibitor sorafenib is used in the therapy of advanced disease. However, the effects of sorafenib are limited, and combination treatments aiming at improved survival are encouraged. The sphingosine analog FTY720 (Fingolimod), which is approved for treatment of multiple sclerosis, has shown tumor suppressive effects in cell lines and animal models of HCC. In the present study, we combined sorafenib with FTY720 in order to sensitize the HCC cell lines Huh7 and HepG2 to sorafenib treatment. Using the XTT assay we show that noncytotoxic doses of FTY720 synergistically enhanced the decrease in viability caused by treatment of both cell lines with increasing doses of sorafenib. Further studies in Huh7 revealed that combined treatment with FTY720 and sorafenib resulted in G1 arrest and enhanced cell death measured using flow cytometry analysis of cells labeled with propidium iodide (PI)/Annexin‐V and PI and 4′, 6‐diamidino‐2‐phenylindole‐staining of nuclei. In addition, signs of both caspase‐dependent and – independent apoptosis were observed, as cotreatment with FTY720 and sorafenib caused cytochrome c release and poly‐ADP ribose polymerase‐cleavage as well as translocation of Apoptosis‐inducing factor into the cytosol. We also detected features of autophagy blockage, as the protein levels of LC3‐II and p62 were affected by combined treatment with FTY720 and sorafenib. Together, our results suggest that FTY720 sensitizes HCC cells to cytotoxic effects induced by treatment with sorafenib alone. These findings warrant further investigations of combined treatment with sorafenib and FTY720 in vivo in order to develop more effective treatment of HCC.